Investigation of the Effect of Friction Stir Spot Welding of BH Galvanized Steel Plates on Process Parameters and Weld Mechanical Properties - Sheikhhasani, H.; Sabet, H.; Abasi, M. (Engineering, Technology & Applied Science Research, 2016)
This study evaluates the effect of Friction Stir Spot Welding (FSSW) pin shape on overlapping galvanized BH plates. FSSW is done at 4, 6 and 9 seconds dwell time at two rotational speeds (1500 and 1800 rpm) by tools with 10 and 14 mm shoulder diameter. Microstructural properties (OM and SEM), Vickers micro hardness and tension are tested on the welded spots. By increasing shoulder diameter from 10 to 14 mm to joint two plates, microstructural grain size decreases by 23% in SZ and 15% in TMAZ. Maximum fracture increases as shoulder diameter increases to 32%.